“We Are in the Middle of Two Great Powers”: Refugees, Activists, and Government during the Plattsburgh Border Crisis of 1987 - Rosinbum, John (Refuge: Canada’s Journal on Refugees, 2015)
In early 1987 the Canadian government closed its border to hundreds of would-be refugees streaming north from the United States. Forced to flee the newly passed Immigration Reform and Control Act, refugees from Central America, Southeast Asia, and eastern Africa found themselves trapped between the two countries. This article examines the reasons for the Canadian government’s policy shift, the temporary refugee camp it created in upstate New York, and the camp’s effect on the border town of Plattsburgh, NY.